PERAN AKTOR DALAM IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR DI JALAN PANDANARAN - Febriyanto, Arief Dwi; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2017)
Charges for parking is payment for the use of service parking lots determined by the government .The goal is to increase their own the area of a city semarang .The trouble is who is actors are involved in of policy parking retribution in Pandanaran Street and all its role? The purpose of this research is to find actors are involved in of policy parking retribution in Pandanaran Street .In addition to know factors driving & impediment to the implementation of the parking retribution policy. This study adopted qualitative approaches , type research descriptive .The research results show that actors in the implementation of the policy parking retribution is the office of transportation,non civil servants who were recruited Departement of Transportation Semarang City,Civil service police Unit, Police , army , and the community . The role of transportation department as the manager of policy is to engage directly in levies parking , determine the prevailing vehicle , handle illegal parking and impose sanction to motorists parked in any place. The role of non civil servants as the manager of policy is getting a help civil servant transportation department in the of levies parking and find parking lot new if needed.Than Civil service police Unit personnel as the manager of policy is coordinate with transportation department in the joint of levies parking and control Illegal Parking.The role of police as the manager of policy is getting a help in the combined in the control of illegal park .And the role of army is helping in the combined in the park controlling wild and raid bus of having no complete with coordinated with the police.The role of the people of them provide recommendations, approval and consideration related charges for parking then over if there are illegal parking.